The Relationship Between Patients’ Knowledge and Medication Adherence and Asthma Control at the Pulmonary Clinic of Pasar Minggu Regional General Hospital - Dinaryanti, Ratna Sari; Pratiwi, Atika (Jurnal Kesehatan dan Kedokteran, 2026)
Asthma control is often suboptimal in routine care, and gaps in patient knowledge and medication adherence may contribute to poor control. Objective: This study aimed to examine the relationship between patients’ asthma knowledge level and medication adherence with asthma control among adult patients attending the Pulmonary Clinic of Pasar Minggu Regional General Hospital. Methodology: A quantitative cross-sectional design was used with consecutive sampling of 191 adult asthma patients. Data were collected using validated questionnaires: ACQ-5, AGKQ, and MMAS-8. Descriptive statistics summarized distributions, and Chi-square tests examined associations between knowledge and asthma control, and between adherence and asthma control. Findings: Most participants had uncontrolled asthma (56.0%), low asthma knowledge (55.0%), and low medication adherence (56.5%). Knowledge level was significantly associated with asthma control (p = 0.001), with uncontrolled asthma more prevalent in the low-knowledge group (70.5%) than the high-knowledge group (38.4%). Medication adherence was also significantly associated with asthma control (p = 0.001), with uncontrolled asthma more common among low adherence (67.6%) than moderate (41.4%) or high adherence (38.5%). Implications: Integrating structured education and adherence-support strategies into routine outpatient care may improve asthma control and reduce exacerbation risk. Originality: This study integrates asthma knowledge and medication adherence within the same analytic framework of asthma control in an Indonesian pulmonary-clinic population, providing context-specific evidence for targeted clinic-based interventions.